Assessment of minimum oxygen concentrations for the growth of heat-resistant moulds. (December 2019) - Santos, Juliana Lane Paixão dos; Samapundo, Simbarashe; Pimentel, Gabriela Cadore; Van Impe, Jan; Sant'Ana, Anderson S.; Devlieghere, Frank
Abstract: This study evaluated the effect of both gaseous and dissolved oxygen (O2 ) concentration (0 - 21%) on the growth of six heat-resistant moulds (HRMs) ( Neosartorya and Byssochlamys spp.) previously isolated from high-acid fruit products. The study was performed in acidified potato dextrose agar (aPDA) with all six HRMs and with B. fulva and N. fischeri in strawberry, apple and orange juice-based media. At ≥ 0.15% O2, visible growth of the HRMs occurred within 3–6 days. Complete inhibition on aPDA did not occur even at very low levels of dissolved O2 ( ca . 0.01% O2 ). With the exception of B. fulva, decrease of the O2 concentration to ≤0.03% resulted in significantly (p < 0.05) longer times to visible growth. The growth of N. laciniosa, N. fischeri, B. nivea and B. fulva was inhibited for 30 days when they were incubated under strict anaerobic conditions . As in aPDA, B. fulva and N. fischeri grew in the three fruit-based media at O2 concentrations ≥0.15%. Significantly slower (p < 0.05) growth was observed for N. fischeri in orange juice medium. Strategies to inhibit the growth of HRMs should therefore not be based entirely on establishing low headspace O2 levels. With this in mind, the effect of low O2 concentrations (<1%) should be studied in combination with other factors (hurdles) such as antioxidants, organic acids, sugars (aw ), storage temperature and pasteurization intensity, in order to predict the growth inhibition of the HRMs. Highlights: The effect of O2 level (0–0.9%) on growth of 6 HRMs was assessed. All strains grew at very low O2 levels (0–0.15%). Low O2 levels delayed growth of the HRMs for up to 30 days. Growth of the HRMs was only inhibited under strict anaerobic conditions. Depletion of O2 significantly increased the times to growth in fruit-based medium.